Blurred Boundaries: Toning Ethics in News Routines. (18th November 2019) - Ferrucci, Patrick; Taylor, Ross
ABSTRACT: This study investigates how United States-based professional photojournalists apply toning ethics in their news routines and whether those ethics vary by organization. Utilizing data collected from in-depth interviews with professional photojournalists and a hierarchy of influences framework, we found that while some ethical decisions are embedded in photojournalists' news routines, these do vary greatly by organization. These findings illustrate how journalistic norms could be potentially changing and that individual news organizations are applying ethics differently.